SNCA variants and alpha-synuclein level in CD45+ blood cells in Parkinson’s disease - Emelyanov, A.; Kulabukhova, D.; Garaeva, L.; Senkevich, K.; Verbitskaya, E.; Nikolaev, M.; Andoskin, P.; Kopytova, A.; Milyukhina, I.; Yakimovskii, A.; Timofeeva, A.; Prakhova, L.; et al. (Journal of the neurological sciences, 2018)
Parkinson's disease (PD) is the second most frequent neurodegenerative disorder. Impaired metabolism of alpha-synuclein (SNCA) and its aggregation are implicated in PD pathogenesis. SNCA has been identified as a highly significant genetic risk loci associated with the sporadic form of PD in across populations in GWAS and replicative studies. In this study we conducted a genetic analysis of five SNCA single nucleotide polymorphisms (SNPs) (rs356219, rs2619364, rs11931074, rs2583988, rs356168) in 458 PD patients and 353 from North-West region of Russia. We also assessed an association of studied SNPs with alpha-synuclein levels in homogeneous cell fraction of CD45+ blood cells in PD patients and controls. An association with PD was shown for SNPs rs356219, rs11931074, rs356168. After correction for covariates the significant association with the disease only for rs11931074 and rs356168 was shown. Alpha-synuclein level in peripheral blood CD45+ cells was significantly increased in PD patients compared to control subjects (р = 0.02). The effect of SNCA rs356219 and rs356168 on CD45+ alpha-synuclein level in PD patients and control groups was shown. At the same tame the increase of CD45+ alpha-synuclein level in PD patients was revealed only in risk allele carriers as for rs356219 and rs356168 SNPs. Therefore, our study was the first that demonstrated the increased level of alpha-synuclein in CD45+ blood cells in PD patients and showed that it could be influenced by SNCA rs356168 and rs356219. In conclusion we confirmed the significance of the SNCA locus in the PD development. •SNCA SNPs rs356219, rs2619364, rs11931074, rs356168 are associated with PD.•CD45+ alpha-synuclein is increased in sporadic PD patients.•CD45+ alpha-synuclein in PD patients could be influenced by SNCA rs356168 and rs356219.